Opredelitev in stališča otrok do internetne pornografije - Erjavec, Karmen (Šolsko polje, 2011)
Because there is no international study on children's definition of pornography in the literature, this research seeks to fill this gap. This study used detailed semi-structured interviews with twenty-two twelve-year-olds to reveal the definition of pornography and the impacts on children's views, and then examined the key differences between the sexes. The research showed that boys' definition of pornography is closer to the liberal definition of pornography, which emphasizes sexual arousal and an explicit display of sexuality. The girls had what seemed to be a feminist definition, which emphasizes the objectification and subjugation of women to men. This is only seemingly a feminist definition because, unlike the feminist authors that were interviewed, the girls accept their subjugation as desired behavior. The threshold of perceiving and consuming pornography is unsuitably lower in girls than in boys because they particularly stated that the features of porn chic are pornographic. Boys understand conversation and watching internet pornography as something normal, but they have trouble distinguishing between "real" sexuality and pornographic internet messages. Girls are more critical towards the definition of pornography as "real" sexuality. An aesthetic criterion is most important in determining the acceptability of pornographic scenes. The difference by sex is evident in the acceptability/refusal of pornography because for girls the pornography that is watched by boys is ugly, dirty, and abnormal, but boys define their consumption as "childish". The interviewees used a biological model to explain gender diff erences regarding pornographic consumption: males have a biological need, which forces them touse pornography and be promiscuous. The results show that the interviewees have established a distinctive and hierarchical understanding of male and female gender roles.
Keywords: Mass media; Množični mediji; Children; Internet; Otroci; child; Pornography; Pornografija; Media literacy; Medijska pismenost